Imaginário e design: resignificação do jogo eletrônico por meio da linguagem expressiva - Sato, Adriana Kei Ohashi (2007)
This work intends to analyze design as the object that generates answers to the user's (gamer's) expectations based on the collective imaginarium. In turn, this imaginarium originates in a specific social-cultural context. Considering men as symbolic beings, they look for the reason of their existence by attribuing meaning to objects. Those meanings are interpreted by society, creating values, behaviors and cultural references. This work presents fundamental concepts about design and its presence in the social-cultural context, being design the language that interprets and re-signify the electronic game based on the collective imaginarium.